Comparison of time-restricted feeding and Islamic fasting: a scoping review - Ismail, Suriani; Abdul Manaf, Rosliza; Mahmud, Aidalina (World Health Organization, 2019)
Background: Research on the health benefits of fasting is growing; this includes time-restricted feeding and Islamic fasting. Aims: This article aims to review and highlight the similarities and differences between time-restricted feeding and Islamic fasting during Ramadan. Methods: A scoping review was undertaken to identify relevant articles that answered the research question: what are the similarities and differences in characteristics of time-restricted feeding and Islamic fasting? MEDLINE/PubMed was searched using the terms: time-restricted feeding, and weight. Inclusion criteria were: original research and review articles; written in English; and published between the years 2000 and 2017. Results: A total of 25 articles that answered the research question were included in the review: 15 original research papers and 10 reviews. The findings suggest that Ramadan fasting is a form of time-restricted feeding in the contemporary context because of the period when eating is not allowed. The fasting duration reported in time-restricted feeding ranged from 4 to 24 hours, which is longer than that of Islamic fasting which is between 8 and 20 hours. Both time-restricted feeding and Islamic fasting have been found to have positive health effects, including weight reduction. Conclusion: Time-restricted feeding and Islamic fasting have many similar characteristics and reported positive health effects.